2012
DOI: 10.1051/0004-6361/201219368
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter imaging of submillimeter galaxies in the COSMOS field: redshift distribution

Abstract: We present new IRAM Plateau de Bure interferometer (PdBI) 1.3 mm continuum observations at ∼1.5 resolution of 28 submillimeter galaxies (SMGs), previously discovered with the 870 μm bolometer LABOCA at the APEX telescope from the central 0.7 deg 2 of the COSMOS field. Nineteen out of the 28 LABOCA sources were detected with PdBI at a > ∼ 3σ level of ≈1.4 mJy/beam. A combined analysis of this new sample with existing interferometrically identified SMGs in the COSMOS field yields the following results: i) > ∼ 15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
269
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 138 publications
(302 citation statements)
references
References 99 publications
(237 reference statements)
29
269
4
Order By: Relevance
“…Their relative contribution to this plot is given by the large line-filled red square on the right. Chapin et al, 2009) and the red is from AzTEC sources in COSMOS (Smolčić et al, 2012). The solid dark blue histogram represents both spectroscopic and optical photometric redshifts for AzTEC sources in GOODS-S who suggest the distribution is a log-normal in nature with median value z = 2.6 (solid green line).…”
Section: Redshift Distributions Of 850µm-14 Mm-selected Dsfg Populatmentioning
confidence: 99%
See 1 more Smart Citation
“…Their relative contribution to this plot is given by the large line-filled red square on the right. Chapin et al, 2009) and the red is from AzTEC sources in COSMOS (Smolčić et al, 2012). The solid dark blue histogram represents both spectroscopic and optical photometric redshifts for AzTEC sources in GOODS-S who suggest the distribution is a log-normal in nature with median value z = 2.6 (solid green line).…”
Section: Redshift Distributions Of 850µm-14 Mm-selected Dsfg Populatmentioning
confidence: 99%
“…One more notable analysis of the 1.1 mm-selected population is summarized by Smolčić et al (2012) who describe interferometric follow-up observations of DSFGs in the COSMOS field. Like the interferometric work on the Laboca CDFS sample from ALMA (summarized in Karim et al, 2013;Hodge et al, 2013b), the Smolčić et al work measures the accuracy of previous counterpart identifications to bolometer-detected sources and identifies submillimeter multiples (see more in § 2.5).…”
Section: Redshift Distributions Of 850µm-14 Mm-selected Dsfg Populatmentioning
confidence: 99%
“…Once multi-wavelength counterparts have been identified, photometric redshifts are derived through fitting an SED to the available photometry, allowing redshift to vary as a free parameter (e.g. Smolčić et al 2012). Whilst observationally inexpensive and thus desirable for large SMG surveys, the errors from photometric redshifts are often significant, and samples are again biased by requiring detection in photometric bands.…”
Section: Simulated Observations Of Smgs 1785mentioning
confidence: 99%
“…Atacama Large Millimetre Array -ALMA; Plateau de Bure Interferometer -PdBI; Sub-Millimetre Array -SMA) targeted at single-dish detected sources have indicated that the resolution of single-dish telescopes had in some cases blended the sub-mm emission of multiple galaxies into one single-dish source (e.g. Wang et al 2011;Smolčić et al 2012;Hodge et al 2013). Karim et al (2013) showed the effect this blending has on the observed sub-mm number counts, with the single-dish counts derived from the Large APEX (Atacama Pathfinder EXperiment) BOlometer CAmera (LABOCA) Extended Chandra Deep Field-South (ECDFS) Sub-millimetre Survey (LESS; Weiß et al 2009) exhibiting a significant enhancement at the bright end relative to counts derived from the ALMA followup (ALESS).…”
Section: Introductionmentioning
confidence: 99%
“…), 6 GHz VLA (Myers et al, in prep. ), and the deep multiwavelength X-ray to mm photometry (Scoville et al 2007;Koekemoer et al 2007;Hasinger et al 2007;Capak et al 2007;Sanders et al 2007;Bertoldi et al 2007;Elvis et al 2009;Ilbert et al 2013;McCracken et al 2012;Scott et al 2008;Aretxaga et al 2011;Smolčić et al 2012;Miettinen et al 2015;Civano et al 2016;Laigle et al 2016, Capak et al, in prep. ) and more than 97 000 optical spectroscopic redshifts (Salvato et al, in prep.…”
Section: Introductionmentioning
confidence: 99%